Food protein hydrolysates as a source of dipeptidyl peptidase IV inhibitory peptides for the management of type 2 diabetes. Issue 1 (17th October 2013) - Power, Orla; Nongonierma, A. B.; Jakeman, P.; FitzGerald, R. J.
Abstract : The prevalence of type 2 diabetes mellitus (T2DM) is increasing and it is estimated that by 2030 approximately 366 million people will be diagnosed with this condition. The use of dipeptidyl peptidase IV (DPP-IV) inhibitors is an emerging strategy for the treatment of T2DM. DPP-IV is a ubiquitous aminodipeptidase that cleaves incretins such as glucagon like peptide 1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP), resulting in a loss in their insulinotropic activity. Synthetic DPP-IV drug inhibitors are being used to increase the half-life of the active GLP-1 and GIP. Dietary intervention is accepted as a key component in the prevention and management of T2DM. Therefore, identification of natural food protein-derived DPP-IV inhibitors is desirable. Peptides with DPP-IV inhibitory activity have been identified in a variety of food proteins. This review aims to provide an overview of food protein hydrolysates as a source of the DPP-IV inhibitory peptides with particular focus on milk proteins. In addition, the proposed modes of inhibition and structure–activity relationship of peptide inhibitors are discussed. Milk proteins and associated peptides also display insulinotropic activity and help regulate blood glucose in healthy and diabetic subjects. Therefore, milk protein derived peptide inhibitors may be a unique multifunctional peptide approach for the management of T2DM.